Effect of Iron and Molybdenum Fertilization on Growth, Yield, and Protein Content of Faba Bean (Vicia faba L.) Grown in Gypsum Soil - Al-Janabi, Sura Hameed Bahar (American Journal of Botany and Bioengineering, 2026)
A field experiment was conducted during the 2024–2025 growing season in gypsum soil belonging to the College of Agriculture, Tikrit University, to study the effect of iron (Fe) and molybdenum (Mo) on growth, yield, and protein concentration in broad bean plants. Iron was added at 0, 3, 6, and 12 kg ha⁻¹, and molybdenum at 0, 2, 4, and 8 kg ha⁻¹. The results showed that increasing iron levels led to a significant improvement in all studied traits, with plant height increasing from 70.25 cm at 0 kg ha⁻¹ to 84.38 cm at 12 kg ha⁻¹, leaf area from 3285 cm² plant⁻¹ to 5317 cm² plant⁻¹, plant dry weight from 13.50 g plant⁻¹ to 20.50 g plant⁻¹, and the number of bacterial nodules from 16 plant nodules⁻¹ to 34 plant nodules⁻¹. Grain yield increased from 3141 kg ha⁻¹ to 3929 kg ha⁻¹, and pod yield from 8057 kg ha⁻¹ to 10620 kg ha⁻¹, while the protein concentration in the grains increased from 17.6% to 23.1%. Regarding the effect of molybdenum, the average levels (4 kg ha⁻¹) showed the highest significant improvement in all traits, with plant height reaching 83.90 cm, leaf area 4787 cm² plant⁻¹, dry weight 18.64 g plant⁻¹, number of nodes 31 plant⁻¹, grain yield 3764 kg ha⁻¹, pod yield 10174 kg ha⁻¹, and protein concentration 21.4%. The interaction between the two elements showed a clear and significant effect, with the treatment (Fe 12 kg ha⁻¹ × Mo 4 kg ha⁻¹) giving the highest values for all traits: plant height 92.10 cm, leaf area 6218 cm² plant⁻¹, dry weight 22.95 g plant⁻¹, number of nodes 38 plant⁻¹, grain yield 4187 kg ha⁻¹, pod yield 11725 kg ha⁻¹, and protein concentration 24.5%.